The Teacher's Role in Increasing Student Motivation in Learning Mathematics for Fourth Grade Students at SD N Gotakan - Hengkang Bara Saputro; Siti Nurwita Sekar Suci (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
The teacher plays an important role in fostering student motivation to learn by always actively encouraging and encouraging students in the class during the teaching and learning process or learning takes place. This study aims to describe the teacher's role in increasing students' motivation to learn mathematics and the supporting and inhibiting factors of teachers in increasing learning motivation in students' mathematics learning. This study uses a qualitative method with a survey approach. The object of research is the role of the teacher in increasing learning motivation in learning mathematics for grade IV students. Data collection techniques through observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman models which include data reduction, data presentation, and drawing conclusions. The results of the study show that the teacher has carried out his role well. The role played by the teacher in increasing students' motivation to learn mathematics is the role of the teacher as a source of learning, the role of the teacher as a facilitator, and the role of the teacher as a motivator. Factors supporting the teacher's role in increasing motivation to learn mathematics include infrastructure, student awareness, and support from school members and parents. Factors inhibiting the teacher's role in increasing learning motivation in learning mathematics include the behavior of students who lack discipline and student motivation that has not grown.